Influencing Factors Affecting Performance in Sustainable Manufacturing among Malaysian Companies: A Conceptual Study - Ang, Hong Loong; Lada, Suddin; Wang, Kehui; Li, Xinyue (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research investigates the influence of sustainable manufacturing factors on the performance of manufacturing companies in Malaysia, with a specific focus on sustainable innovation, quality, cost efficiency, delivery, and operational flexibility. Grounded in the Dynamic Capabilities theory, it provides valuable insights that are pertinent to academia, policymakers, and the Malaysian manufacturing sector. The primary goal is to provide a conceptual framework for sustainable manufacturing that could improve organizational performance. Employing a qualitative approach, the study lays the foundation for a comprehensive understanding of these factors and their intricate relationships. It is important to emphasize that this research currently lacks empirical validation, necessitating further investigations to evaluate the applicability of Dynamic Capabilities, sustainable innovation, and flexibility in predicting organizational performance. Subsequent studies should consider incorporating quantitative methodologies and diverse, representative samples to bolster the generalizability of findings. This study underscores the critical significance of sustainable innovation and flexibility in molding organizational performance, highlighting the imperative need for their integration into sustainable manufacturing strategies. Furthermore, it equips manufacturing company stakeholders with valuable insights to refine their strategic communication pertaining to the advantages of sustainable manufacturing. The research not only offers substantial guidance to policymakers, industry practitioners, and the academic community but also underscores the urgency of further empirical research to confirm and expand upon these conceptual insights.